An Omega-3-rich Anti-inflammatory Diet Improved Widespread Allodynia and Worsened Metabolic Outcomes in Adult Mice Exposed to Neonatal Maternal Separation. (1st August 2021) - Eller, Olivia C.; Foright, Rebecca M.; Brake, Aaron D.; Winter, Michelle K.; Bantis, Leonidas E.; Morris, E. Matthew; Thyfault, John P.; Christianson, Julie A.
Highlights: An anti-inflammatory diet improved pain-related outcomes in female mice that experienced early life stress. Male mice had reduced perigenital allodynia on an anti-inflammatory diet, regardless of neonatal maternal separation. Female mice gained more weight, adiposity, and had evidence of systemic inflammation on an anti-inflammatory diet. Male mice had increased weight, adiposity, and inflammation on diets with or without anti-inflammatory components. Abstract: Inflammation plays a key role in the progression and maintenance of chronic pain, which impacts the lives of millions of Americans. Despite growing evidence that chronic pain can be improved by treating underlying inflammation, successful treatments are lacking and pharmaceutical interventions are limited due to drug side effects. Here we are testing whether a 'healthy human' diet (HHD), with or without anti-inflammatory components (HHAID), improves pain-like behaviors in a preclinical model of chronic widespread hypersensitivity induced by neonatal maternal separation (NMS). The HHD and HHAID are isocaloric and macronutrient-matched, have a low glycemic index, and fat content (35 kcal%) that is high in omega-3 fatty acids, while only the HHAID includes a combination of key anti-inflammatory compounds, at clinically relevant doses. Mice on these diets were compared to mice on a control diet with a macronutrient composition commonly used in rodents (20% protein, 70% carbohydrate, 10% fat). Our results demonstrate a benefit of the HHAID on pain-like behaviors in both male and female mice, despite increased caloric intake, adiposity, and weight gain. In female mice, HHAID specifically increased measures of metabolic syndrome and inflammation compared to the HHD and control diet groups. Male mice were susceptible to worsening metabolic measures on both the HHAID and HHD. This work highlights important sexual dimorphic outcomes related to early life stress exposure and dietary interventions, as well as a potential disconnect between improvements in pain-like behaviors and metabolic measures.